Mobilizing Social Groups and Popular Organizations for Economic Recovery and Self Reliance of Nigeria. (Journal of Science and Technology, 2015)
The major contribution made in the organization is that social groups and popular organizations should operate as co-operatives were possible. These co-operatives can be used to (i) achieve increased domestic production of food, industrial raw materials and manufactured products; (ii) contribute to the process of making decisions which affect the lives of the masses; (iii) assist in instilling discipline and professional ethnics in the members of the different organizations and the community.